Promotion mix : level of awareness and purchase likelihood - Wong, Anne Ling Ling (Universiti Malaysia Sarawak (UNIMAS), 2011)
Promotion strategies were used by many companies to promote their products to the consumers. This paper examines the consumer’ attitude on promotional mix elements which are advertising, personal selling, sales promotion, publicity/public relation and direct marketing and the impact of these attitude toward consumers’ level of awareness and purchase likelihood, without focusing on any specific products in Kuala Lumpur, Malaysia. The theoretical frameworks used in this research were Marketing Theory and Theory of Reasoned Action (TRA). Primary data were collected by using questionnaire. 400 questionnaires were collected and analyzed using Correlation and Regression. Hypothesis 1 stated that there is a significant positive relationship between consumers’ attitude on sales promotion and publicity and level of awareness and this hypothesis was accepted. Hypothesis 2 stated that consumers’ attitude on advertising, personal selling, sales promotion and publicity/public relations will influence their purchase likelihood of products and it also was accepted. Hypothesis 3 stated that consumers’ attitude on direct marketing influences the purchase likelihood of products and it was rejected. One of the reasons was consumer less intention to purchase the products after go through the direct marketing (Alnawas, 2010).